Early Plasma Soluble Receptor for Advanced Glycation End‐Product Levels Are Associated With Bronchiolitis Obliterans Syndrome. Issue 3 (17th January 2013) - Shah, R. J.; Bellamy, S. L.; Lee, J. C.; Cantu, E.; Diamond, J. M.; Mangalmurti, N.; Kawut, S. M.; Ware, L. B.; Christie, J. D.
<x xml:space="preserve">Abstract</x> Early epithelial injury after lung transplantation may contribute to development of bronchiolitis obliterans syndrome (BOS). We evaluated the relationship between early postoperative soluble receptor for advanced glycation end‐product (sRAGE) levels, a marker of type I alveolar cell injury and BOS. We performed a cohort study of 106 lung transplant recipients between 2002 and 2006 at the University of Pennsylvania with follow‐up through 2010. Plasma sRAGE was measured 6 and 24 h after transplantation. Cox proportional hazards models were used to evaluate the association between sRAGE and time to BOS, defined according to ISHLT guidelines. Sixty (57%) subjects developed BOS. The average time to BOS was 3.4 years. sRAGE levels measured at 6 h (HR per SD of sRAGE: 1.69, 95% CI: 1.11, 2.57, p = 0.02) and 24 h (HR per SD of sRAGE: 1.74, 95% CI: 1.14, 2.65, p = 0.01) were associated with an increased hazard of BOS. Multivariable Cox regression indicated this relationship was independent of potential confounders. Elevated plasma sRAGE levels measured in the immediate postoperative period are associated with the development of BOS. Early epithelial injury after transplantation may contribute to the development of fibrosis in BOS.